THE EFFECT OF COMPOST FERTILIZER AND EFFECTIVE MICROORGANISMS 4 DOSES ON GROWTH AND YIELD OF PAKCOY (Brassica rapa L.) - Sri Hariningsih Pratiwi (Gontor AGROTECH Science Journal, 2018)
The purpose of this research was to find out the compost fertilizer and effective microorganisms 4 dosesin order to obtain the optimal growth and yield of pakcoy. The research was conducted at Klampisan Rejo, Kraton-Pasuruan on the altitude of ± 6,7 msl in June–August 2016. This research arranged by factorial treatments. The first factor was the doseof compost (K) namely; K1 (30 tons ha-1), K2 (40 tons ha-1) and K3 (50 tons ha-1) and the second factor was the dose of EM4 (D) namely; D1 (10 ml l-1), D2 (20 ml l-1) and D3 (30 ml l-1), so there were 9 combinations of treatments. This research used Randomized Completely Block Design which each combination was repeated three times. The results showed there was interaction between compost fertilizer and EM4dosetreatment on the number of leaveson age 28th day and weight of the total dry plant on age 14th day. The highest production was in 40 tons ha-1dose of compost which 5,27 ton ha-1, followed by 30 tons ha-1 dose of compostwhich produce 4,29 ton ha-1and the lowest yield was in 50 tons ha-1 dose of compost which produce 3,62 ton.ha-1, Mean while for the dose of EM4 treatment, the highest yields was from 20 ml l-1 dose of EM4 which produce 5,10 ton ha-1, followed by 30 ml l-1 dose of EM4 which produce 4,52 ton ha-1 and the lowest yield was from 10 ml l-1 dose of EM4 which produce 3,56 ton ha-1. Keywords:pakcoy,dose,compost, EM4